Clinical and Radiological Assessment of Patients with Lung Cancer Using Chest CT Scan: An Observational Study in a Barcelona Hospital, Spain - Banos, Stephanie (Phlox Institute: Indonesian Medical Research Organization, 2024)
Introduction: Lung cancer is one of the most common and deadliest types of cancer in the world. Chest CT scan is an important diagnostic tool for detecting and evaluating lung cancer. This study aimed to assess the clinical and radiological characteristics of patients with lung cancer who underwent chest CT scans at Barcelona Hospital, Spain. Methods: This research is a retrospective observational study involving 1059 patients diagnosed with lung cancer who underwent chest CT scans between 2018-2023. Patient data were collected from electronic medical records, including demographic information, clinical symptoms, CT scan findings, and histopathological diagnosis results. Results: The most common clinical symptom was cough (83.0%), followed by shortness of breath (58.8%), chest pain (45.6%), coughing up blood (20.3%), and weight loss (17, 9%). The most common CT scan finding was lung nodules (80.6%), followed by consolidation (39.7%) and pleural effusion (26.9%). The most common histopathologic diagnosis was adenocarcinoma (40.4%), followed by squamous cell carcinoma (29.5%), large cell carcinoma (17.9%), and neuroendocrine cell carcinoma (12.3%). Conclusion: This study provides an overview of the clinical and radiological characteristics of patients with lung cancer who underwent chest CT scans at the Barcelona Hospital, Spain. The findings of this study may help doctors in diagnosing and managing patients with lung cancer.